Video Copywriting of Pempek Cek Yeti - Andini, Mia Puja (Politeknik Negeri Sriwijaya, 2024)
ABSTRACT: This study discusses the video copywriting process of Pempek Cek Yati using the modified Research and Development (R&D) method by Sukmadinata (2019). The purpose of this study was to outline the steps involved in creating the video copywriting, focusing on three stages: (1) Preliminary study; (2) Model Development; and (3) Product Drafting. There were seven experts of scriptwriting, English, and video editing participated in providing comments and suggestions chosen by purposive sampling. The data were collected by both observation, and interviews, and analyzed through a coding analysis by (Gale, Heath, Cameron, Rashid, & Redwood, 2013 and Furber, 2010). The findings revealed some areas needing improvement, as identified by each expert. The language experts suggested fixing some grammatical error in some parts of ad copy. The video experts suggested revising some parts of video such as changing the filter, adding the logo of institution, the size of subtitle, and adding contact person information. This video copywriting is expected to provide detailed information of Pempek Cek Yati. Keywords: Copy Writing, Culinary Tourism, Pempek Cek Yati, Research and Development, Video